Kinerja Operasional PPS Bungus: Kunjungan Kapal dan Produksi Ikan Tahun 2001-2017 - Puti Lindo Jati; Azmi Fitrisia (Jurusan Sejarah FIS UNP, 2020)
Bungus is one of six the samudera fishery harbour in Indonesia. To operation the Samudera harbour should be follow the mission, aim and target. This article wants to proving the concistantion of program. Especially the coming of the fishey ship and fsh production in Samudera Bungus fishery harboar between the year 2001 until the year 2017. The reseacrh was using history method that consist of 4 process; heuristic, critic, interpretation and historiography. Many data had collect to this research likes each year of report of Bungus Samudera office and interview recording. The critic proces had only comparing data. The thirth method proces is analysis of fact and historiograhy depend of sistematic of the writing likes chapters. The result of the research is Fishery Harbour Samudera Bungus had low grate coming of the ship and fish production comparing of other fishery harbour in Indonesia.